Wind Velocity Induced Stable and Unstable Periodic Oscillations in a Harmonically Excited Aeroelastic Energy Harvester - Yu, Bo (Journal of Vibration Testing and System Dynamics, 2026)
This study explores the periodic oscillations occurring in a piezoelectric energy harvester exposed to a blend of fluid and harmonic force, with a specific focus on the system’s responses to varying wind velocity. A coupled single degree of freedom model for the electromechanical system is presented. For the external forces, both periodic excitation and aerodynamic galloping are considered. The nonlinear differential equations are discretized, and the expressions of periodic responses are derived through the implicit mapping method. The periodic responses are calculated using the Newton-Raphson method. By assessing the eigenvalues of the resultant matrix derived from the mapping structures, the stabilities and bifurcations of these periodic responses are determined. Furthermore, the study investigates how the displacement and voltage nodes of the energy harvester respond to variations in free stream velocity and excitation amplitude. Maximum eigenvalue magnitudes are also presented for stability assessment. Additionally, utilizing the periodic nodes of displacement and voltage, the harmonic amplitudes are calculated using Fast Fourier Transform, illustrating their variation with changes in free stream velocity. Finally, the study compares implicit maps and numerical simulations for both stable and unstable responses.